Diversity of Wood-decay Fungi and Investigation of Heart-rot Fungi in Hongneung Forest - Ye-Yeong Kim; Mi-Jeong Park; Yeongseon Jang; Kang-Hyeon Ka (한국균학회지)
Urban forests play a crucial role in environmental improvement, recreation, and education. However, their development has led to decreased biodiversity and forest simplification. Reduced biodiversity increases vulnerability to pathogens, especially heart-rot fungi, which decompose tree tissues, weaken, and ultimately topple trees. In this study, we investigated the diversity of wood-decay fungi, including heart-rot fungi, in an urban Hongneung Forest. A total of 94 samples were collected and identified through morphological and molecular analyses of the internal transcribed spacer (ITS) region of the DNA sequences. A total of 32 species, 26 genera, 18 families, and 11 orders were identified. Most species belonged to Polyporales, accounting for 59% (19 species) of all species. At the genus level, Perenniporia, Neohypochnicium, Coniophora, Ceratobasidium, and Scytinostroma were the most prevalent. Heart-rot fungi, which decay living trees, constituted 13% of all species observed, including Bjerkandera adusta, Coniophora arida, Perenniporia fraxinea, and Somion delectans. These fungi were primarily distributed in the lower parts or trunks of trees. Nucleotide-level ITS sequence analysis identified genetic differences between C. arida (four specimens) and P. fraxinea (five specimens). Two C. arida and four P. fraxinea variants were found in the forests. This study provides baseline data on the diversity of wood-decay fungi in Hongneung Forest, which can be used for future research on heart-rot fungi in urban Korean forests.